2015
DOI: 10.1016/j.joca.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Targeted mutation of NOV/CCN3 in mice disrupts joint homeostasis and causes osteoarthritis-like disease

Abstract: SummaryObjectiveThe matricellular protein NOV/CCN3, is implicated in osteoarthritis (OA) and targeted mutation of NOV in mice (Novdel3) leads to joint abnormalities. This investigation tested whether NOV is required for joint homeostasis and if its disruption causes joint degeneration.MethodNOV expression in the adult mouse joint was characterized by immunohistochemistry. A detailed comparison of the joints of Novdel3−/− and Novdel3+/+ (wild-type) males and females at 2, 6 and 12 months of age was determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
(52 reference statements)
0
21
0
Order By: Relevance
“…However, our finding that both treatment with recombinant CCN3 and CCN3 overexpression significantly increased the p53 expression indicates that p53 regulation by CCN3 also occurs in chondrocytes. The other CCN3-deficient mice caused by deletion of exon 3 showed skeletal abnormalities in some joints and heart defects [ 30 ]; 12-month-old male knee joints showed some degenerative changes, but female joints did not [ 31 ]. Since these CCN3-deficient mice were able to express the first 1 and 2 domains coded by exon 1 and 2, the phenotypes of these mice must be interpreted with care.…”
Section: Discussionmentioning
confidence: 99%
“…However, our finding that both treatment with recombinant CCN3 and CCN3 overexpression significantly increased the p53 expression indicates that p53 regulation by CCN3 also occurs in chondrocytes. The other CCN3-deficient mice caused by deletion of exon 3 showed skeletal abnormalities in some joints and heart defects [ 30 ]; 12-month-old male knee joints showed some degenerative changes, but female joints did not [ 31 ]. Since these CCN3-deficient mice were able to express the first 1 and 2 domains coded by exon 1 and 2, the phenotypes of these mice must be interpreted with care.…”
Section: Discussionmentioning
confidence: 99%
“…Using the targeted mutation mice model of CCN3, Roddy K.A. et al have also reported that CCN3 is required for maintenance of articular cartilage and for joint homeostasis [24]. …”
Section: Discussionmentioning
confidence: 99%
“…CCN3 is essential for maintaining HSC long term repopulating activity and bone marrow engraftment (Gupta et al, 2007). Finally, CCN3 is also known to participate in chondrogenesis (Heath et al, 2008;Hoshijima et al, 2012;Janune et al, 2017Janune et al, , 2011Kawaki et al, 2008;Lafont et al, 2005;Roddy and Boulter, 2015), osteogenesis (Heath et al, 2008;Matsushita et al, 2013;Minamizato et al, 2007;Ouellet and Siegel, 2012;Rydziel et al, 2007) and dentin regeneration .…”
Section: Roles Of Ccn3 In Tissue Regenerationmentioning
confidence: 99%